Creating Shared Value Svara Resonance: Digitalisasi Musisi Jalanan Surabaya - Teno, Jenny Putri Yunlin; Yusuf, Muhammad Azizi; Wijayanti, Renata; Duhita, Amanda Ridha Pradya (Pusat Riset dan Inovasi Nasional, 2026)
The creative economy plays a crucial role in building the national economy, yet many creative economy players, particularly street musicians, remain untouched by digitalization. Svara Resonance is a Creating Shared Value (CSV) initiative organized by Airlangga University Master of Management students aimed at enhancing the capacity of street musicians through a digitalization and personal branding workshop combined with auditions and media publications. The implementation method included preparation, workshop implementation, and auditions. The results demonstrated the active participation of five selected international musicians, an increased understanding and application of personal branding during performances, and economic benefits in the form of financial appreciation for participants. The initiative also garnered publicity from ten online media outlets and one television channel, expanding the reach of social impact and exposure for the organization. Discussions demonstrated that Svara Resonance successfully integrated social interests with the university’s core business, in line with the principle of creating shared value. This initiative demonstrates that CSV activities can be social investment that benefits both the community and the organization.